Anemia Due to Low-Iron Affects Cognitive Capacity of Adolescent Girls Schooling in Secondary Schools in Sokoto, Nigeria - Miya, Yusuf Yahaya; Butuwo, Thomas Murma; A., Abdullateef Abdullahi; Ukwak, Blessing Godwin (Asian Journal of Science, Technology, Engineering, and Art, 2024)
Anemia is a problem occurring due to poor iron intake or hereditary sickle cells threating public health in many adolescents and adults. Anemia is able to affect cognitive ability of people especially adolescents (youngsters). This study evaluates the effect of iron-deficiency anemia and sickle cell anemia on cognition of some adolescents schooling girls from Sokoto, Nigeria. The study consisted of recruitment of 80 girls (40 normal, and 40 anemic) subjected to Montreal Cognitive Assessment. 10 girls diagnosed with sickle cell anemia and 25 normal girls were assessed with Montreal cognitive assessment. The mean marks of the respondents were noted; therewith, chi-square test revealed significant difference at (p<0.05). The anemic girls earned less mean marks (400.0 ± 13.0) compared to the normal girls (960.0 ± 25.0). The healthy participants in the study scored higher marks (945.0 ± 10.0) than the sickle cell anemia patients (90.0 ± 3). Therefore, anemia is of the potential to affect cognitive capacity of schooling girls in Sokoto. Nutritional and related interventions are important, because poor cognition may affect education and overall potential of girls to be keys in growth and development of societies.